ShakerVis: Visual analysis of segment variation of German translations of Shakespeare’s Othello - Geng, Zhao; Cheesman, Tom; Laramee, Robert S.; Flanagan, Kevin; Thiel, Stephan (Information visualization, 2015)
William Shakespeare is one of the world’s greatest writers. His plays have been translated into every major living language. In some languages, his plays have been retranslated many times. These translations and retranslations have evolved for about 250 years. Studying variations in translations of world cultural heritage texts is of cross-cultural interest for arts and humanities researchers. The variations between retranslations are due to numerous factors, including the differing purposes of translations, genetic relations, cultural and intercultural influences, rivalry between translators and their varying competence. A team of Digital Humanities researchers has collected an experimental corpus of 55 different German retranslations of Shakespeare’s play, Othello. The retranslations date between 1766 and 2010. A sub-corpus of 32 retranslations has been prepared as a digital parallel corpus. We would like to develop methods of exploring patterns in variation between different translations. In this article, we develop an interactive focus + context visualization system to present, analyse and explore variation at the level of user-defined segments. From our visualization, we are able to obtain an overview of the relationships of similarity between parallel segments in different versions. We can uncover clusters and outliers at various scales, and a linked focus view allows us to further explore the textual details behind these findings. The domain experts who are studying this topic evaluate our visualizations, and we report their feedback. Our system helps them better understand the relationships between different German retranslations of Othello and derive some insight.